Clinical and functional outcomes and treatment options for paediatric elbow dislocations: Experiences of three trauma centres. (July 2015) - Subasi, M.; Isik, M.; Bulut, M.; Cebesoy, O.; Uludag, A.; Karakurt, L.
Abstract: Although elbow dislocations are seen rarely in children, their management remains controversial. In this study, over a 7 years period, we evaluated retrospectively the clinical and functional results of paediatric elbow dislocations managed in three different trauma centres. Pure dislocations and dislocations with associated injuries were evaluated separately. In total 56 patients met the inclusion criteria. The number of patients without additional injury was 22 out of which according to the Robert's criteria, 15 children (68%) had an excellent, four (18%) a good, one (5%) a fair, and two (9%) a poor outcome. From the thirty-four patients that had associated injuries, two (6%) had an excellent, 6 (18%) a good, 10 (29%) a fair and 16 (47%) a poor result. Overall, patients with pure dislocation were found to have a better range of motion compared to patients with dislocation and associated injuries. Prolonged follow ups, and effective rehabilitation programs are required in order to expect good outcomes.